2013
DOI: 10.1158/1055-9965.epi-13-0434
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Omega-3 and Omega-6 Concentrations and Risk of Cutaneous Basal and Squamous Cell Carcinomas in Australian Adults

Abstract: Laboratory-based evidence suggests that omega-3 and omega-6 polyunsaturated fatty acids may affect skin photocarcinogenesis, but epidemiologic evidence is inconsistent. In 1,191 White Australian adults, we prospectively investigated associations between baseline plasma concentrations of omega-3 and omega-6 fatty acids and cutaneous basal cell carcinomas (BCC) and squamous cell carcinomas (SCC). Relative risks (RR) and 95% confidence intervals (CI) were estimated on the basis of number of histologically confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The detailed process of study selection is presented in Supplementary Figure S1. Forty-one articles reported RRs for n-6 PUFA intake only [ [24,53,58,75,80], endometrium (3 articles and 1756 cases) [31,36,85], skin (3 articles and 36,819 cases) [23,39,44], and others (ovarian, lung, liver, lymphoma, and gastric; 6 articles and 2958 cases) [25,30,47,51,83,90]. Three articles provided RRs of any type of cancer [22,38,73].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed process of study selection is presented in Supplementary Figure S1. Forty-one articles reported RRs for n-6 PUFA intake only [ [24,53,58,75,80], endometrium (3 articles and 1756 cases) [31,36,85], skin (3 articles and 36,819 cases) [23,39,44], and others (ovarian, lung, liver, lymphoma, and gastric; 6 articles and 2958 cases) [25,30,47,51,83,90]. Three articles provided RRs of any type of cancer [22,38,73].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Summary of pooled relative risks (RR) of cancer risk for n-6 polyunsaturated fatty acid (PUFA) intake. PUFAs and the risk of cancer[24,[26][27][28]32,35,38,39,[41][42][43]47,51,52,55,56,61,62,67,68,70,71,73,74,76,82,84,88,89] (Supplementary…”
mentioning
confidence: 99%
“…A prospective cohort study evaluated associations between plasma phospholipid levels of n -3 and n -6 PUFAs and the development of NMSC. The results showed a reduced risk of SCC in patients with high EPA concentrations and omega-3/-6 ratio and an inverse association of total omega-6 and BCC risk [ 354 ]. However, a study of over 40,000 American male health professionals failed to find a link between n -3 PUFA intake and BCC risk [ 355 ].…”
Section: Inflammation and Skin Cancermentioning
confidence: 99%
“…The higher composition of 18:2 n-6 and n-6 PUFAs were associated with increased risk for prostate cancer and breast cancer, but that of AA had no association [ 19 ]. Animal studies indicate that n-6 PUFA increase carcinogenesis [ 23 ]. Adds to evidence from animal studies, our results are consistent with a case-control study which reported a significantly higher risk of SCC with greater AA concentrations in erythrocytes membranes [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in risk of SCC with increased intake of diets with a high n-3/n-6 ratio was reported in a population-based case-control study [ 20 ]. Ratio of n-3/n-6 in circulation plays a key role in determining the overall effect on skin photocarcinogenesis [ 23 ].…”
Section: Discussionmentioning
confidence: 99%